The 10th ambassadorial lecture series (ALS) by His Excellency Vanu Gopala Menon Singapore’s High Commissioner to Malaysia / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
On behalf of the Vice–Chancellor of UiTM, Professor Datuk Ts. Dr Hajah Roziah Mohd Janor, I am pleased to welcome everyone to the 10th Ambassadorial Lecture Series organised by the Department of International Affairs (DIA), UiTM Global. Professor Datuk sends her warmest regards to everyone. 2. It is a great honour to be here today and to welcome our distinguished guest, His Excellency Vanu Gopala Menon, The High Commissioner of Singapore to Malaysia who will speak on “Singapore-Malaysia Relations and Our Role in ASEAN.”